2014
DOI: 10.1134/s0021364014150089
|View full text |Cite
|
Sign up to set email alerts
|

Elementary excitations in the symmetric spin-orbital model

Abstract: Possible types of elementary excitations in the symmetric spin-orbital model on the a square lattice are analyzed using a spherically symmetric self-consistent approach. The excitation spectra are calculated. The behavior of the corresponding correlation functions depending on the temperature and parameters of the model is studied. A schematic phase diagram is plotted. It is shown that the thermodynamics of the system is mainly determined by elementary excitations with the entangled spin and orbital degrees of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 26 publications
(37 reference statements)
2
40
0
1
Order By: Relevance
“…Unfortunately this type of pairing is much weaker in two dimensional systems, and in the weak-coupling regime only a fragile superconducting state at O(U 3 ) exists 4 . However, partially polarizing a two dimensional electron gas (2DEG) with an in-plane magnetic field can dramatically increase the strength of the effective pairing interaction at O(U 2 ), as has been shown by a perturbative diagrammatic expansion 5 and more recently by an asymptotically exact renormalization group approach 6,7 . It was found that a non-unitary p + ip superconducting state forms, in which the larger of the 2DEG's two energy bands superconducts, while the smaller one does not.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately this type of pairing is much weaker in two dimensional systems, and in the weak-coupling regime only a fragile superconducting state at O(U 3 ) exists 4 . However, partially polarizing a two dimensional electron gas (2DEG) with an in-plane magnetic field can dramatically increase the strength of the effective pairing interaction at O(U 2 ), as has been shown by a perturbative diagrammatic expansion 5 and more recently by an asymptotically exact renormalization group approach 6,7 . It was found that a non-unitary p + ip superconducting state forms, in which the larger of the 2DEG's two energy bands superconducts, while the smaller one does not.…”
Section: Introductionmentioning
confidence: 99%
“…The strong Coulomb interactions and the relativistic spinorbit interaction entangle locally the spin and orbital degrees of freedom [13] which display an amazing variety of fundamentally new and fascinating phenomena, ranging from topologically nontrivial states [14], relativistic Mott-insulating behavior in 5d [15,16] and 4d [17,18] transition-metal oxides and entanglement on superexchange bonds in spin-orbital models [6,19]. Other more recent developments include entangled spin-orbital excitations [20,21], doped spin-orbital systems [22], skyrmion lattices in the chiral metal MnSi [23], multiferroics, spinHall effects [24], Majorana and Weyl fermions [25], topological surface states [26], Kondo systems [27], exotic spin textures in disordered systems, to name just a few.…”
Section: Introductionmentioning
confidence: 99%
“…Estimate (15) is surprisingly low because a decrease in Γ ch below ~10 -1 s -1 was always considered impossible not only under natural but also under artificial (radio-frequency [3][4][5][6], laser [7,8]) conditions. Nevertheless, this level is reached in a natural, rather than artificial, way.…”
Section: Strong Natural Suppressionmentioning
confidence: 99%
“…In this case, the application of long-lived isomers under natural conditions is possible neither in a γ-ray laser (see, e.g., [2][3][4][5][6][7][8][9][10][11][12]) nor in γ-resonance spectroscopy [1,13,14] because the cross section for resonance processes decreases by a factor of k = Γτ > 1 + Γ dd τ + … ≫ 1. Here, Γ is the total linewidth, k is the relative total width, and τ is the lifetime of the isomer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation